Construct validity of tests that measure kick performance for young soccer players based on cluster analysis: exploring the relationship between coaches rating and actual measures - Palucci Vieira, L. H.; de Andrade, V. L.; Aquino, R. L.; Moraes, R.; Barbieri, F. A.; Cunha, S. A.; Bedo, B. L.; Santiago, P. R. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The main aim of this study was to verify the relationship between the classification of coaches and actual performance in field tests that measure the kicking performance in young soccer players, using the K-means clustering technique.